The Effects of Income Inequality and Redistribution in Democracies: A Dynamic Panel Data Approach - Aslan, Goksu (Dynamic Econometric Models, 2017)
In this paper, the simultaneous effects of the inequality and redistribution on economic growth are tested for the whole sample and for a subset of democratic countries, following system-GMM estimation on a panel dataset over a period from 1960 to 2010. Overall, net inequality has a negative significant effect on subsequent 5 years for both samples, while redistribution impact is only significant in democracies. The findings are related to the fact that in democracies, the governments tend to significantly redistribute more.